The Review of Symbolic Interactionism Theory an Adolescent Self-Actualization through Korean Popular Culture - Lidya Widiarti; Anindya P. P.; Genoveva P. K. (Jurnal Komunikasi dan Bisnis, 2023)
Korean Popular or often abbreviated as K-Pop, the fever is not only felt only in Indonesia, but has gone global. The craze for K-Pop music and Korean drama movies is an inseparable part of Korean fever in various countries. Korean popular culture fever also affects fashion in Indonesia, this can be seen from young people in Indonesia who often imitate Korean fashion. The desire of young people to follow this style of Korean popular culture fashion gives rise to an achievement of their self-actualization. Many teenagers imitate the Korean style, ranging from hairstyles, clothing models, accessories, to lifestyle and how to interact with peers. This is because they really like Korean popular culture such as Korean movies, Korean boy bands, to top Korean stars. One of the reasons is the beauty of the style or style of the film players and boy bands, the beauty of the appearance and physique of the stars, and the dramatic and unique storyline of Korean films. The theory of symbolic interactionism has three concepts, namely mind, self, and society, where these three concepts are strongly influenced by the interpretation of others who make contact or interact with us. The emergence of popular Korean culture is used as a symbol of interaction followed by young Jakartans. The clothes we wear, the way we walk and talk, the work we do, are perceived by others as symbols we build to tell others about who we really are. Who we are is called self-concept (Jones, 2001:145). The concept of interactionism is a guideline to analyze the self-actualization of Jakarta's youth. They fulfill their self-actualization needs, that is, fulfill their desire to be what they want to be.